Health-Promoting Nature of Lactococcus lactis IBB109 and Lactococcus lactis IBB417 Strains Exhibiting Proliferation Inhibition and Stimulation of Interleukin-18 Expression in Colorectal Cancer Cells - Sałański, Przemysław; Kowalczyk, Magdalena; Bardowski, Jacek K.; Szczepankowska, Agnieszka K. (Frontiers in Microbiology, 2022)
Lactic acid bacteria (LAB) are Gram-positive bacteria which are considered for use as adjuvant therapeutics in management of various disease ailments, including obesity, irritable bowel syndrome, lactose intolerance and cancer. To investigate the possible use of Lactococcus lactis strains from our collection in treatment of gastrointestinal cancer, we tested them for the ability to arrest proliferation of human colorectal adenocarcinoma cells (Caco-2). Results of the BrdU assay showed that the anti-proliferative activity of L. lactis cells is strain-specific. We found that particularly, two strains, L. lactis IBB109 and L. lactis IBB417, exhibited the most potent inhibitory effect. Moreover, both strains triggered interleukin 18 gene expression, normally inhibited in Caco-2 (cancer) cells. To examine the probiotic potential of the two strains, we tested them for bile salts and acid tolerance, as well as adhesion properties. Both isolates exhibited probiotic potential – they survived in the presence of 0.3% bile salts and tolerated exposure to low pH and osmotic stress. Notably, we found that L. lactis IBB417 displayed better adherence to mucus and Caco-2 cells than L. lactis IBB109. Additionally, by microdilution tests we confirmed that both strains are sensitive to all nine antibiotics of human and veterinary importance listed by the European Food Safety Authority. Finally, by in silico investigations of whole genome sequencing data, we revealed the genetic features of L. lactis IBB109 and L. lactis IBB417 that can be associated with functional (e.g., adhesion and carbohydrate metabolic genes) and safety (e.g., virulence and antibiotic resistance) aspects of the strains, confirming their health-promoting potential.